2014
DOI: 10.1080/10408398.2011.651177
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Macronutrient Metabolism

Abstract: The biological differences between males and females are determined by a different set of genes and by a different reactivity to environmental stimuli, including the diet, in general. These differences are further emphasized and driven by the exposure to a different hormone flux throughout the life.These differences have not been taken into appropriate consideration by the scientific community. Nutritional sciences are not immune from this “bias” and when nutritional needs are concerned, females are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 176 publications
(191 reference statements)
0
45
0
2
Order By: Relevance
“…It has been suggested that sex itself (sex hormones affect the amount and distribution of body fat) is a factor influencing body composition, its oxidation and mobilization [20]. In our study, the increased risk to males may also be due to the different pattern of PA [19] or to different dietary habits of men and women.…”
Section: Discussionmentioning
confidence: 64%
“…It has been suggested that sex itself (sex hormones affect the amount and distribution of body fat) is a factor influencing body composition, its oxidation and mobilization [20]. In our study, the increased risk to males may also be due to the different pattern of PA [19] or to different dietary habits of men and women.…”
Section: Discussionmentioning
confidence: 64%
“…Sieber and Spradling (10) recently revealed that ecdysone‐ and EcR‐mediated signaling controls lipid metabolism, to establish a female metabolic state and to promote whole‐body triglyceride storage, which has been linked to increased survival (49). The presence of sex steroid hormones in humans is also recognized as playing a major role in establishing sex‐specific differences in body composition (50). Prunetin led to an increase in fat body mass, as indicated by an upregulation of total triglycerides of 29% compared with controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As such, reproductive‐steroid‐induced changes in the metabolome, small molecules that are fundamental to cell signaling and function, may represent a significant albeit indirect means by which steroids regulate processes relevant for brain and behavior. Animal and cell culture studies, in fact, suggest both sex differences and an effect of reproductive steroids in the metabolism of proteins that affect a broad range of pathological and physiological events (Comitato, Saba, Turrini, Arganini, & Virgili, ; Smith et al., ).…”
Section: Discussionmentioning
confidence: 99%